Synthesis and swelling behaviour of rice husk based superabsorbent polymer composite - Hong, Yuen Fatt (2012)
This research is about Synthesis and Swelling Behaviour of Rice Husk Based Superabsorbent Polymer Composite(SPC).In this research,the results for swelling behavior of SPC were reported.The objectives of the research are to study the optimum synthesizing condition of rice husk based SPC by determining the effect on amount of initiator,crosslinker and rice husk towards water absorbency.SPC sample is prepared by solution polymerization technique where acrylic acid-acrylamide-rice husk(AA-AM-RH)mixture is reacted with N,N-methylenebisacrylamide(MBA)and Ammonium persulfate (APS) under nitrogen atmosphere with effective stirring for 3 hours of reaction.Data for analytical evaluation were thoroughly analyzed.The water absorbency of the SPC samples was determined by tea-bag method.The SPC were characterized by using Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscope(SEM)and Thermogravimetric Analysis(TGA).The result of the 3 parameters involved yield a bell shape graph where there is an optimum value of these 3 parameters towards maximum water absorbency of SPC.The optimum content to produce highest yield of water absorbency are 1wt% of APS content,1wt% of MBA content and 20wt% of rice husk content which achieved 22.219g/g,12.823g/g, and 11.109g/g of water absorbency respectively.This study showed a new method in utilizing crops residues such as rice husk in the production of superabsorbent material.